Selectivity of the New Catalyst ZnO-MCM-48-CaO in Esterification of Calophyllum inophyllum Oil - La Kolo; Firdaus Firdaus; Paulina Taba; Muhammad Zakir; Nunuk Hariani Soekamto (Universitas Muhammadiyah Magelang, 2022)
The synthesis of MCM-48 containing surfactants (CTAB and Triton X-100), ZnO, and CaO aimed to find a potential heterogeneous catalyst in the esterification of Calophyllum inophyllum oil to biodiesel. This research is important in the production of biodiesel from vegetable oils with more than 2% free fatty acids (FFA), such as Calophyllum inophyllum oil using heterogeneous catalysts. Synthesis of heterogeneous catalysts, MCM-48 and ZnO-MCM-48-CaO (ZMC), using the hydrothermal method at various calcination temperatures was conducted to find the optimum calcination temperature for the reaction. The activity of the catalyst in the reaction was determined using acid-base titration methods and GC-MS. The MCM-48 catalyst calcined at 650 Â°C (MCM-48/650) had a catalytic activity of 35.74% and was selective for converting linoleic acid in Calophyllum inophyllum oil to biodiesel. In addition, this catalyst was also capable of cracking the compounds contained in Calophyllum inophyllum oil into suitable hydrocarbons for biodiesel. In the esterification of vegetable oils, four heterogeneous catalysts (MCM-48/550, ZMC/550, ZMC/650, and ZMC/750) had the potential to replace conventional catalysts (H2SO4), particularly in the generation of biodiesel from Calophyllum inophyllum oil.